The Intellectual Legacy of Abd al-Rauf al-Fanshuri: Tafsir, Islamic Law, and Sufism in the Malay World - Zainuddin, Anayya Syadza; Kamaruddin, Kasimah Binti; Zainuddin, Zainuddin (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2024)
Abd al-Rauf al-Fanshuri al-Jawi was one of the most influential scholars in the intellectual and religious history of the Malay world, recognized as a Quranic exegete, jurist, and Sufi master. This study provides a comprehensive analysis of his contributions, including his biography, scholarly networks, exegetical methodology, and his role in Islamic law and Sufism. Using a systematic literature review based on documentary analysis, this research examines various academic sources to understand Abd al-Rauf’s intellectual approach and its impact on the development of Islam in the Nusantara. The findings reveal that Abd al-Rauf’s legacy extends beyond Turjuman al-Mustafid, the first complete Quranic exegesis in Malay-Jawi, to the dissemination of Islamic knowledge through his extensive network of scholars and students. His exegetical methodology integrates textual and contextual approaches, with an emphasis on tauhid, Sufism, and Islamic law, fostering a balanced and contextualized interpretation of Islam within the socio-cultural framework of the Malay world. The findings highlight the need for further research on Malay-Jawi exegesis and comparative studies with other interpretative traditions in the broader Islamic world.